Multicultural Education at Al-Mubarok Dormitory Darul Ulum Islamic Boarding School Jombang - Saihul Atho Alaul Huda; Tomi Ariffaturakhman (SCHOOLAR: Social and Literature Study in Education, 2021)
Multicultural has the meaning of cultural diversity, various politeness. In terminology, multicultural education can be interpreted as education about cultural diversity. Pesantren integrates the curriculum that comes from the government and the pure curriculum of the pesantren with the aim of equipping its students not only in tafaqquh fi al din but also in general knowledge. Likewise, the journey in implementing Islamic values ​​does not only stand on the foundation of the holy texts of the Qur'an and Hadith.